Psalms 73-150 : an exegetical and theological exposition of holy scripture - Estes, Daniel J. (Nashville : B & H Publishing Group, 2019)
Dan Estes's new work on the Psalms is an exceptional addition to this valuable series. Not only is he extremely qualified to write such a work because much of his scholarly work has been done in the Psalms for more than three decades, but he is also qualified by his love for the church, which will be aided greatly by his present work. This commentary on one of the most beloved books in the Old Testament is very thorough. It deals with current debates in the Psalms and yet is practical for gaining insights into the meaning of each of the psalms. Especially helpful will be the Response section for each of the psalms that provides clear guidance on how to apply the psalm for today. --Paul D. Wegner, Distinguished Professor of Old Testament, Gateway Seminary of the Southern Baptist Convention.
Book III: Psalms 73-89 -- Book IV: Psalms 90-106 -- Book V: Psalms 107-150.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 19, 2019).
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Biblical Studies -- Wisdom Literature; Commentaries; Criticism, interpretation, etc